Clinical features and outcomes of nine children with acute necrotizing encephalopathy - Yahua Zhang; Lei He; Jingran Xu; Piaosi Wang; Hehe Chen (Frontiers in Pediatrics)
ObjectiveTo report the clinical features, cranial imaging findings, treatment approaches and outcomes of pediatric acute necrotizing encephalopathy (ANE) to improve early diagnosis and treatment strategies of this rare but severe condition.MethodsRetrospective analysis of nine children with ANE, admitted to the Pediatric Intensive Care Unit (PICU) of Women's and Children's Hospital of Ningbo University (2019–2024) was performed. Clinical presentations, laboratory results, neuroimaging results, treatment modalities, and outcomes were retrospectively evaluated. Survivors were followed up and their function evaluated using the Pediatric Overall Performance Category scale.ResultsPatients (age range 9 months to 14 years) predominantly presented with fever, seizure and altered consciousness. Influenza A was the most common antecedent infection. All cases progressed to symmetric multifocal lesions, with elevated inflammatory markers like interleukin-6 (IL-6). Brain magnetic resonance imaging (MRI) typically showed symmetric bilateral thalamic lesions. Acute necrotizing encephalopathy Severity Score (ANE-SS), a severity index based on neurological symptoms, shock, and brainstem involvement, was significantly lower in survivors than in non-survivors (P < 0.05). Survivors received early immunomodulatory treatments, including high-dose methylprednisolone, intravenous immunoglobulin (IVIG), and plasma exchange (PLEX). The overall mortality rate was 56%. Survivors showed significant neurological improvement after rehabilitation therapy.ConclusionANE occurs commonly after influenza. Yet, many many children have influenza, and not many have ANE.It is typically presents with bilateral thalamic lesions and systemic inflammation.Hyperpyrexia and inflammatory markers are valuable prognostically indicators, and ANE-SS accurately predicts mortality risk. Early combined immunomodulatory therapy and rehabilitation may improve outcomes. These findings contribute to the understanding of clinical and imaging predictors and allow early identification, prognostication, and individualized management.